Impact of Experience and Participation in Extension Programming on Perceptions of Water Quality Issues - Pei-wen Huang; Alexa J. Lamm (Journal of International Agricultural and Extension Education, 2015)
Water is an essential resource for human activities and the global ecosystem. However, issues related to water quality have been reported internationally for quite some time with little to no action taken by the public to alter practices to ensure a future sustainable water supply. International extension educators have taken a role in educating about water quality but issues continue to exist. In order to understand current public perceptions of water quality issues and the influence of extension programming, an online survey was conducted in Florida, a part of the U.S. where water is readily accessible but water quality issues are pervasive, leading to a disconnect between what the public thinks about water and the realities of the water scarcity situation. Individuals’ experiences with water quality issues, participation in extension programs, perceptions on water quality, and the importance of clean water were collected and the relationships were examined. The findings indicated respondents who had experienced water quality issues perceived water quality was getting worse and that clean water was important. However, the respondents who had participated in extension programs perceived water quality was getting better, but their perceptions of the importance of clean water were inconsistent based upon their extension programming engagement. Recommendations provide insight into how international extension educators can enhance public awareness of water quality issues globally through programming designed to drive behavior changes that will result in enhanced water quality around the world.
Keywords: Water Quality; Public Awareness; Experience